Kilcrea Abbey and Bridge - Willes. W., artist; Hall, S. C., Mrs., 1800-1881 (1840)
View of Kilcrea Abbey from across the river, including a bridge and women with a basket.
Title inscribed l.r. on sheet.
Attributed to W. Willes.
Catalogue of Irish Topographical Prints and Original Drawings / Rosalind M. Elmes ; New edition revised and enlarged by Michael Hewson - Dublin : Malton Press, 1975
Ireland: its scenery, character, &c / Mr. & Mrs. S. C. Hall - London: How and Parsons, 1841-43
Keywords: Churches -- Ireland -- Cork (County) -- 1830-1840; Bridges -- Ireland -- Cork (County) -- 1830-1840; Cork (Ireland : County); Ink drawings -- Irish -- 1830-1840.; Wash drawings -- Irish -- 1830-1840